Sequence element enrichment analysis to determine the genetic basis of bacterial phenotypes - John A. Lees (Nature Portfolio, 2016)
Plasticity and clonal population structure in bacterial genomes can hinder traditional SNP-based genetic association studies. Here, Corander and colleagues present a method to identify variable-length sequence elements enriched in a phenotype of interest, and demonstrate its use in human pathogens.